Information quality and conservatism in accounting earnings published in Brazil - Coelho, Antonio Carlos; Lima, Iran Siqueira (Revista Contabilidade & Finanças, 2007)
The article evaluates the practice of conservatism in the earnings presented in the accounting reports published in Brazil in the period from 1995 to 2004. The research is carried out in view of the fact that, on the one hand, Brazilian regulation emphatically establishes the principle or convention of conservatism - to anticipate the recording of losses and postponing the recognition of gains; on the other, it allows for the premature recognition of revenues not yet confirmed, like in the case of asset reevaluations. The research tested the asymmetrical timely anticipation of economic losses through the model of Basu (1997) and conditional conservatism through the model of association between accruals and cash flows (BALL; SHIVAKUMAR, 2005). The sample considers public and private companies with data for the complete time series, regressing panel data according to more adjusted methods. The results confirm the hypothesis that the managers of the sample companies do not adopt conditional conservatism, although evidences of greater reversal of transitory components of earnings are found in the case of negative variations in antecedent earnings.